IDENTIFIKASI TENAGA KERJA YANG KEHILANGAN UPAH/PENDAPATAN SELAMA PANDEMI COVID-19 - Riyadi Solih (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The COVID-19 pandemic that has hit Indonesia since March 2020 until now has had an impact on various fields of life, including employment. Many studies have examined the impact of COVID 19 on employment, but large-scale studies using probability sampling techniques are still rare. This study examines the impact of COVID-19 on fluctuations in wages/income for Indonesian workers. The information used comes from the August 2021 National Labor Force Survey (Sakernas) conducted by BPS-Statistics Indonesia (BPS) in 34 provinces in Indonesia. The results confirm that around 29 percent of workers earn less than before the COVID-19 pandemic. The results of logistic regression show that low education, employment in the manufacture sector, housing in urban areas, and the status of casual workers during the COVID-19 pandemic all tend to reduce wages/income